2009
DOI: 10.1007/s11044-009-9156-4
|View full text |Cite
|
Sign up to set email alerts
|

Linearization and parametric vibration analysis of some applied problems in multibody systems

Abstract: The paper deals with the application of the Runge-Kutta method for calculating steady-state periodic vibrations of the parametric vibration systems governed by linearized differential equations. The numerical calculation is also demonstrated by two models of multibody systems and measurements on real objects. Good agreement is obtained between the numerical and experimental results. Consequently, the obtained results can also be applicable to investigate other complicated models of multibody systems which perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…When analyzing systems with elasticities, it is usually assumed that the elastic links are weightless and are characterized by constant coupling rigidity, i.e., the proportionality coefficient between the moment (force) and deformation [6,7,8]. In other cases, it is assumed that the material has a constant mass, but can change its stiffness due to temperature changes [9,10].…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing systems with elasticities, it is usually assumed that the elastic links are weightless and are characterized by constant coupling rigidity, i.e., the proportionality coefficient between the moment (force) and deformation [6,7,8]. In other cases, it is assumed that the material has a constant mass, but can change its stiffness due to temperature changes [9,10].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The electric drive of the horizontal looper is a multimass system that cannot be reduced to a two-mass system [8,15,16]. When analyzing the electric drive system of a horizontal looper, it is necessary to take into account changing the rigidity of the strip as a distributed mechanical system with decreasing or increasing its length in the drive.…”
Section: Developing the Modelmentioning
confidence: 99%
“…To verify the calculating results using the numerical methods, the dynamic load moment of the mechanical adjustment unit was measured on the driving shaft (see also Figure 16). A typical record of the measured moment is plotted in Figure 20, together with the curves calculated from the dynamic model by using the WKB-method [18,34], the kinesto-static calculation and the proposed numerical procedures based on Newmark method and Runge-Kutta method. Comparing the curves displayed in this figure, it can be observed that the calculating result using the numerical methods is more closely in agreement with the experimental result than the results obtained by the WKB-method and the kinesto-static calculation.…”
Section: Periodic Vibration Of the Transport Manipulator Of A Forgingmentioning
confidence: 99%
“…Equations ( 31) represent a set of constraint conditions between the unknown (boundary) constants, a n , b n ,..., g n and h n , and the Fourier expansion coefficients A mn , B mn , and C mn ( m, n = 0, 1, 2,... ). The constraint equations (31a-h) can be rewritten more concisely, in matrix form, as = Ly Sx (34) Vibrations of Cylindrical Shells http://dx.doi.org/10.5772/51816…”
Section: An Approximate Solution Based On the Rayleigh-ritz Proceduresmentioning
confidence: 99%
“…The one-dimensional extended rod theory for the transverse motion takes the coupled equations concerning v , ϕ , and u * , as given in Eqs. (32) to (34). Now consider the equation of motion expressed in terms with the lateral deflection.…”
Section: Simplification Of Governing Equationmentioning
confidence: 99%